A Study on the Effect of a Structured Educational Program on Menstrual Hygiene Awareness Among Adolescent Girls at Pt. Shri Narayan Pandey Intermediate College, Chaubepur, Kanpur, Uttar Pradesh - Khushboo Chaudhary; Keerti Verma; Jyoti Soni; Tanya Sharma; Anjalee Pratap; Sandhya; Ranika; Kanchan Singh; Niladrita Deb (International Journal of Midwifery Nursing And Practices, 2025)
Menstruation is totally normal and experienced by lots of people worldwide each month. Taking care of your menstrual hygiene is super important for women and girls from their first period to menopause. During those 2–7 days each month, it is essential to practice good menstrual health for avoiding infections, minimizing odors, and staying comfy. Unfortunately, in many places, talking about periods is considered taboo due to traditional beliefs. This lack of discussion makes it tough for girls and women to learn about proper menstrual hygiene practices and maintaining good health during menstruation Poor hygiene can lead to various infections that seriously affect health. One major focus for girls and women is managing menstrual hygiene properly. Maintaining menstrual hygiene with clean and absorbent sanitary products is essential for preventing infections. Alarmingly, many young girls in India continue to rely solely on cloths during their menstrual periods, with some only changing them once a day. A research study was carried out at Pt. Shri Narayan Panday Intermediate College, located in Chaubepur, Kanpur, Uttar Pradesh, which focused on evaluating the impact of a well-organized educational program aimed at improving adolescent girls' understanding of menstrual hygiene. The study sought to assess the effectiveness of this structured teaching initiative in enhancing the knowledge of menstrual hygiene among the participants. Let us spread the word about the importance of menstrual hygiene and help make sure all girls have access to the right information.
Keywords: Adolescent girls; Menarche; hygiene; menstrual; sanitary pads